PENEGAKAN HUKUM PIDANA TERHADAP PELAKU PERSETUBUHAN PADA ANAK (ANALISIS TERHADAP PUTUSAN MAHKAMAH AGUNG NOMOR: 1202 K/PID.SUS/2009) - Panca Hutagalung; Muhammad Hamdan; Mahmud Mulyadi; Utary Maharany Barus (Universitas Sumatera Utara, 2014)
ABSTRACT Law No. 23/2003 on Child Protection is initially intended to protect children and to ensure their safety by providing security for their rights. Nevertheless, sexual harassment toward children often occurs and indicates its escalation even though it is regarded as a felony. How about the regulation on sexual harassment according to the criminal law in Indonesia, how about the enforcement of criminal law in judex facti in the case of sexual harassment toward children under the Verdict No. 2417/Pid.B/2008-Mdn, in conjunction with the Verdict No. 38/Pid/2009/PT-Mdn, and how about the enforcement of criminal law in judex juris on sexual harassment toward children under the Verdict No. 1202K/Pid.Sus/2009.The research used juridical normative method with prescriptive analytic. Sexual harassment toward children is regulated in the Criminal Code, in Law No. 23/2003 on Child Protection, and in Law No. 23/2004 on the Abolition of Violence in Household. The enforcement of criminal law in judex facti under the Verdict No. 2417/Pid.B/2008-Mdn, in conjunction with the Verdict No. 38/Pid/2009/PT-Mdn is in line with law of criminal procedure. Handing down a verdict is based on the authentication theory according to law negatively and follows fault theory although the victim’s fault is not considered. The enforcement of criminal law in judex juris under the Verdict No. 1202K/Pid.Sus/2009 is in line with law of criminal procedure and reflects the theory of the victim’s fault. Keywords: Law Enforcement, Sexual Harassment, Child.